Impact of porous nanomaterials on inhibiting protein aggregation behaviour. Issue 6 (15th January 2021) - Bardhan, Munmun; Dolui, Sandip; Chaudhuri, Siddhi; Paul, Uttam; Bhattacharjee, Gaurav; Ghosal, Manorama; Maiti, Nakul C.; Mukhopadhyay, Debashis; Senapati, Dulal
Abstract : Aggregation of intrinsically disordered as well as the ordered proteins under certain premises or physiological conditions leads to pathological disorder. Abstract : Aggregation of intrinsically disordered as well as the ordered proteins under certain premises or physiological conditions leads to pathological disorder. Here we have presented a detailed investigation on the effect of a porous metallic (Au) and a non-metallic (Si) nanomaterial on the formation of ordered (fiber-like/amyloid) and disordered (amorphous) aggregates of proteins. Porous nanogold (PNG) was found to reduce the amyloid aggregation of insulin but does not have much impact on the lag phase in the aggregation kinetics, whereas porous nano-silica (PNS) was found both to decrease the amount of aggregation as well as prolong the lag phase of amyloid fiber formation from insulin. On the other hand, both the porous nanoparticles are found to decrease the extent of amorphous aggregation (with slight improvement for PNS) of pathogenic huntingtin (Htt) protein in Huntington's disease cell model. This is a noted direct observation in controlling and understanding protein aggregation diseases which may help us to formulate nanotherapeutic drugs for future clinical applications.